POLA PENDIDIKAN INKLUSIF BERBASIS TEKNOLOGI ASISTIF DI SDN - Mhd. Supardi; Lia Yuliana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to describe the pattern of inclusive education based on assistive technology at SDN 016 Muara Wahau. This research employs a qualitative approach with a descriptive research design. The subjects of the study include the principal, classroom teachers, special assistant teachers, students with special needs, regular students, and parents. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the inclusive education pattern applied is a regular classroom model with a differentiated instruction approach. The use of assistive technology in learning is still relatively simple, such as the use of smartphones, visual media, and learning videos; however, it has a positive impact on students’ understanding and participation, especially for students with special needs. Social interaction between regular students and students with special needs is considered good, characterized by mutual assistance and social acceptance. The challenges faced include limited human resources, lack of teacher training, and inadequate facilities and infrastructure. The efforts made by the school are still simple and adaptive. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan pola pendidikan inklusif berbasis teknologi asistif di SDN 016 Muara Wahau. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Subjek penelitian meliputi kepala sekolah, guru kelas, guru pendamping khusus (GPK), siswa berkebutuhan khusus (ABK), siswa reguler, dan orang tua siswa. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pola pendidikan inklusif yang diterapkan adalah model kelas reguler dengan pendekatan diferensiasi pembelajaran. Penggunaan teknologi asistif dalam pembelajaran masih tergolong sederhana, seperti penggunaan smartphone, media visual, dan video pembelajaran, namun memberikan dampak positif terhadap pemahaman dan partisipasi siswa, khususnya ABK. Interaksi sosial antara siswa reguler dan ABK tergolong baik, yang ditandai dengan adanya sikap saling membantu dan penerimaan sosial. Kendala yang dihadapi meliputi keterbatasan sumber daya manusia, kurangnya pelatihan guru, serta keterbatasan sarana dan prasarana. Upaya yang dilakukan sekolah masih bersifat sederhana dan adaptif.